Implementasi Konsep Edu-Fun Pada Pusat Edukasi dan Keterampilan Bagi Komunitas Save Street Child Surabaya - Kantara, Alice; Wardani, Laksmi Kusuma; Basuki, Lucky (Intra, 2019)
In 2017, Indonesia declaims its desire to be free from street children. But, the reality is thatÂ until now this desire has not been realized. When on the streets, there are many risks that must be faced by children. Therefore the Save Street Child (SSC) appears. Save Street Child Surabaya (SSCS) is a driving community for observers of street and marginal children in Surabaya. This community aims to spread awareness and enthusiasm for sharing with street and marginal children. Now, SSCS does not haves a basecamp. Therefore, a facility is needed to supports the achievement of SSCS goals and supports the implementation of community activities through education and skills centre. This design elevates the concept of Edu-Fun with the theme of a city parks. The resulting space is in an the foam of an education center consisting of reading area, library, class and Islamic prayer room; skills center consisting of accessories, confections, batik areas, and painting areas; the area of interest in talent which consists of a table tennis area and areas of interest in singing and dancing and other complementary facilities. This design uses Robert Curedele's design thinking process and methods with the Human Center Design approach through the stages of observe, understand, ideate, prototype, test and implementation.